Macroeconomics : understanding the global economy - Miles, David (David D.); Scott, Andrew, 1965-; Breedon, F. J. (Francis J.) (Chicester, West Sussex : John Wiley and Sons, Inc., 2012)
'A revised and updated edition of a very successful macroeconomics textbook. The authors deal with sophisticated issues using advanced economic theory, but in a manner that is accessible to anyone taking a single course in macroeconomics. They begin with real-world economic issues, and describe why these matter, before embarking on economic theory, ensuring that readers emerge with a good practical understanding of the global economy and how economists think about it'--
Revised edition of: Macroeconomics and the global business environment / David Miles, Andrew Scott. 2nd ed.
Includes bibliographical references and index.
Keywords: Macroeconomics